Modified ceramsite filler based on iron-sulfur autotrophic denitrification as well as preparation method and application of modified ceramsite filler
By using iron-sulfur autotrophic denitrification modified ceramic filler in sewage treatment, combined with limestone and biochar filter structure, the problem of low carbon nitrogen treatment efficiency and secondary pollution than tail water is solved, and efficient The effect of nitrogen removal and phosphorus removal reduces operating costs and sludge generation.
Patent Information
- Application Number
- CN202411363812.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-28
AI Technical Summary
Existing sewage treatment technology is difficult to efficiently treat low-carbon-nitrogen ratio tailwater. Traditional heterotrophic denitrification methods require carbon sources, which have high operating costs and may cause secondary pollution. The single autotrophic denitrification method greatly affects the efficiency of pH changes, and Sulfur-based autotrophics can produce secondary pollution.
Modified ceramic filler based on iron-sulfur autotrophic denitrification is used to form modified ceramic filler loaded with modified ceramic filler by combining iron powder, pyrite powder and biochar as modifications and forming modified ceramic filler loaded with modified ceramic filler for biological filtration The main layer of the pool, combined with the filter layer of limestone and biochar, adjust the pH and enhance the biooxidation effect.
The nitrogen removal and phosphorus removal effect of low-carbon nitrogen ratio wastewater has been significantly improved, and the nitrogen removal rate has been increased by more than 90%, and the phosphorus removal rate has been increased by more than 15%, which has achieved effective treatment of low-carbon nitrogen ratio wastewater, reducing the amount of sludge produced and Secondary pollution improves treatment efficiency and water quality.
Smart Images

Figure CN119219210A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment, and in particular to a modified ceramsite filler based on iron-sulfur autotrophic denitrification, and a preparation method and application thereof. Background Art
[0002] Nitrogen-containing pollutants are one of the main ecological problems in the water environment. The main sources of nitrogen pollution are non-point source pollution during the application of nitrogen fertilizers and point source pollution caused by the discharge of domestic sewage and industrial nitrogen-containing wastewater. Among them, the discharge of low carbon-nitrogen ratio tailwater from urban secondary sewage treatment plants is an important source of nitrogen and phosphorus pollution. A large amount of nitrogen-phosphorus-containing sewage treatment plant tailwater discharged into the water body will cause eutrophication of the water body, forming "water bloom" or "red tide" phenomena, causing the death of aquatic organisms and destroying biodiversity. In addition, nitrate pollution in water bodies can also cause harm to the human body and may induce hemoglobinemia and blue baby disease.
[0003] At present, there are many treatment methods for low carbon-nitrogen ratio wastewater, which are mainly divided into physicochemical method and biological method. Among them, physicochemical method includes membrane separation method (electrodialysis method, reverse osmosis), ion exchange method, chemical oxidation, coagulation and sedimentation method, etc., but these treatment methods have some shortcomings, such as high operating cost, difficult maintenance, easy to produce secondary pollution, etc. Biological method includes traditional heterotrophic denitrification and autotrophic denitrification technology, which is the main means of wastewater denitrification. Among them, the growth and metabolism of heterotrophic denitrifying bacteria in traditional heterotrophic denitrification method depends on organic carbon, which is not suitable for the treatment of low carbon-nitrogen ratio tail water of secondary sewage treatment plant. The addition of organic carbon source will not only lead to high operating cost, but also produce secondary pollution. In the context of pursuing low-carbon technology today, autotrophic denitrification technology without external carbon source plays an increasingly important role in water pollution control. Autotrophic denitrification technology refers to the process in which autotrophic denitrifying bacteria use inorganic carbon (CO2, HCO3 - 、CO3 2- ) as carbon sources, inorganic compounds (S, S 2- ,Fe,Fe 2+ , Fe 3+ , H2, etc.) as electron donors and electron acceptors (NO3 - -N or NO2 - -N) is reduced to N2 in the biological denitrification process. This process does not require an external carbon source and has the advantages of low sludge production and less secondary pollution. Autotrophic denitrification technologies include sulfur-based autotrophic denitrification, iron-based autotrophic denitrification, anaerobic ammonia oxidation and hydrogen-based autotrophic denitrification. Among them, the sulfur-based autotrophic denitrification process produces acid, while iron-based autotrophic denitrification, hydrogen-based autotrophic denitrification and anaerobic ammonia oxidation consume acid. Therefore, a single autotrophic denitrification will cause a large change in pH during the reaction, thereby affecting the denitrification efficiency of autotrophic bacteria and resulting in poor effluent quality. In addition, studies have shown that SO4 is produced during sulfur oxidation. 2- The amount of NO3- -N reduction was positively correlated, indicating that sulfur-based autotrophy would produce secondary pollution. Summary of the invention
[0004] The purpose of the present invention is to provide a modified ceramsite filler based on iron-sulfur autotrophic denitrification and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is: a modified ceramsite filler based on iron-sulfur autotrophic denitrification, wherein the modified ceramsite filler is ceramsite loaded with a modified substance;
[0007] The ingredients of the amendment include iron powder, pyrite powder and biochar;
[0008] The mass ratio of the iron powder, pyrite powder and biochar is 3:6:1;
[0009] The mass ratio of the modified material to the ceramsite is 1.5:1.
[0010] The second technical solution of the present invention is a method for preparing the modified ceramsite filler, comprising the following steps:
[0011] The iron powder, pyrite powder, biochar and cement (binder) are uniformly mixed to obtain a modified product, and the modified product is attached to ceramsite, and the modified ceramsite filler is obtained after curing.
[0012] Furthermore, the curing time is 10 to 12 days; the particle size of the modified ceramsite filler is 5 to 8 mm; and the amount of cement used is 20% of the total mass of iron powder, pyrite powder and biochar.
[0013] The third technical solution of the present invention: an application of the above-mentioned modified ceramsite filler in sewage treatment.
[0014] Furthermore, the sewage is sewage containing nitrogen and phosphorus.
[0015] The fourth technical solution of the present invention: a biological filter for removing nitrogen and phosphorus from sewage, using the above-mentioned modified ceramsite filler as the main layer.
[0016] Furthermore, the biofilter is provided with a main body layer and a filter layer;
[0017] The sewage first passes through the main layer and then the filter layer;
[0018] The thickness ratio of the main layer to the filter layer is 3:2;
[0019] The filter layer is composed of limestone and biochar in a mass ratio of 9:1.
[0020] Furthermore, the particle sizes of the limestone and biochar are both 3 to 5 mm.
[0021] Limestone as filter material can adjust the pH value of effluent; biochar as auxiliary material can enhance the biological oxidation effect.
[0022] The present invention discloses the following technical effects:
[0023] (1) The modified ceramsite filler of the present invention can significantly improve the denitrification and phosphorus removal effect of the biological filter on low C / N (normal carbon-nitrogen ratio is 10-20, C / N ratio is less than 5, which belongs to low carbon-nitrogen ratio) wastewater.
[0024] (2) The present invention greatly improves the denitrification effect of the biofilter on low C / N ratio wastewater by jointly modifying ordinary ceramsite with iron powder (zero-valent iron), pyrite powder and biochar. Under typical experimental conditions, the denitrification rate of the biofilter containing modified ceramsite filler on low carbon-nitrogen ratio wastewater is more than 90% higher than that of the ordinary ceramsite biofilter (Table 2). This is mainly because the divalent iron and sulfur contained in the zero-valent iron and pyrite powder are present on the surface of the modified ceramsite, which can cause the synergistic effect of iron and sulfur autotrophic denitrification. The presence of biochar is conducive to the enrichment and growth of iron and sulfur autotrophic bacteria, thereby further enhancing the synergistic effect of iron and sulfur autotrophic denitrification, achieving a major improvement in the existing ceramsite biofilter denitrification technology, with significant technological progress, and is of great significance for the biological denitrification of low carbon-nitrogen ratio wastewater.
[0025] (3) The modified ceramsite filler prepared by the present invention using iron powder (zero-valent iron), pyrite powder and biochar significantly improves the phosphorus removal effect of the biofilter on low carbon-nitrogen ratio wastewater. Under typical experimental conditions, the phosphorus removal rate of the biofilter containing modified ceramsite filler on low carbon-nitrogen ratio wastewater is more than 15% higher than that of the ordinary ceramsite biofilter (Table 3). This is mainly because both biological phosphorus removal and chemical phosphorus removal occur simultaneously on the surface of the modified ceramsite filler. Iron and sulfur are elements for microbial growth, which are conducive to the growth of iron and sulfur autotrophic bacteria, while biochar has the function of enriching microorganisms. The coupling of the three can promote biological phosphorus removal. Chemical phosphorus removal mainly relies on the reaction and precipitation of iron ions and their hydroxides with phosphate. At the same time, the iron-carbon micro-electrolysis can promote autotrophic denitrification to generate iron ions, thereby improving the phosphorus removal efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1This is a schematic diagram of the structure of the biofilter used in Example 1;
[0028] Figure 2 is the nitrogen removal effect of the biofilter;
[0029] Figure 3 This is the removal effect of phosphorus by the biofilter. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The main component of the pyrite powder used in the present invention is FeS2, and the content of FeS2 is 99wt.%; the pyrite powder also contains a small amount of elements such as cobalt, nickel and selenium, and has a NaCl type crystal structure.
[0036] The silicate cement used in the present invention is PO 42.5 ordinary silicate cement; the particle size of the iron powder is ≤75 μm; the particle size of the pyrite powder is ≤1 mm; and the particle size of the biochar is ≤150 μm.
[0037] Example 1
[0038] A preparation method of modified ceramsite filler based on iron-sulfur autotrophic denitrification:
[0039] (1) Iron powder, pyrite powder and biochar are mixed in a mass ratio of 3:6:1, and then mixed with silicate cement (the amount of silicate cement is 20% of the total mass of the iron powder, pyrite powder and biochar) to obtain a modified product.
[0040] (2) Add a certain amount of ordinary spherical expanded clay (carrier) with a diameter of 4 to 6 mm into the coating machine, start the coating machine, and evenly sprinkle water while the machine is running to moisten the surface of the carrier. Then add the modifier (the mass ratio of the modifier to the ordinary spherical expanded clay is 1.5:1), sprinkle water appropriately, and make the modifier adhere to the expanded clay. After the modifier is evenly attached to the surface of the expanded clay (polymerized into moist spherical particles), naturally cure at room temperature (25°C) for 11 days to obtain a modified expanded clay filler (EF-D) with a particle size of 5 to 8 mm.
[0041] Comparative Example 1
[0042] The same as Example 1, except that the raw materials for preparing the modified product do not contain pyrite powder, and step (1) is specifically as follows:
[0043] The iron powder and the biochar were mixed in a mass ratio of 9:1, and then doped with silicate cement (the amount of silicate cement was 20% of the total mass of the iron powder and the biochar) and mixed evenly to obtain a modified material.
[0044] The modified ceramsite filler prepared by modification in this comparative example is EF-B, and the particle size is 5 to 8 mm.
[0045] Comparative Example 2
[0046] The same as Example 1, except that step (1) is specifically as follows: iron powder, pyrite powder and biochar are mixed in a mass ratio of 9:9:1, and then added with silicate cement (the amount of silicate cement is 20% of the total mass of the iron powder, pyrite powder and biochar) and mixed evenly to obtain a modified product.
[0047] The modified ceramsite filler prepared by modification in this comparative example is EF-C, and the particle size is 5 to 8 mm.
[0048] Effect Example 1
[0049] (1) Construction of biological filter:
[0050] The water inlets at the bottom of four organic glass columns (EF-A, EF-B, EF-C and EF-D) are connected in series with a water inlet tank with a peristaltic pump (water is inletted in a continuous flow manner controlled by the peristaltic pump) through an inlet pipe. A water distribution layer, a main layer and a filtration layer are arranged in the organic glass column. A sampling port and an overflow port are arranged on the upper part of the organic glass column. The sampling port is located on the upper part of the filtration layer, and the overflow port is located on the upper part of the sampling port.
[0051] The filter layer of the plexiglass columns EF-A, EF-B, EF-C and EF-D is composed of limestone (particle size of 3 to 5 mm) and biochar (particle size of 3 to 5 mm) in a mass ratio of 9:1.
[0052] The water distribution layers of the plexiglass columns EF-A, EF-B, EF-C and EF-D are filled with gravel with a particle size of 8 to 10 mm, and a perforated water distribution pipe (perforated pipe) is arranged in the middle of the water distribution layer.
[0053] The main body of the organic glass column EF-A is filled with ordinary spherical ceramsite with a diameter of 4 to 6 mm;
[0054] The material filled in the main layer of the organic glass column EF-B is the modified ceramsite filler EF-B prepared in Comparative Example 1;
[0055] The material filled in the main layer of the organic glass column EF-C is the modified ceramsite filler EF-C prepared in Comparative Example 2;
[0056] The material used to fill the main layer of the organic glass column EF-D is the modified ceramsite filler EF-D prepared in Example 1.
[0057] The dimensions of the plexiglass column are: H (height) = 320 mm, d (diameter) = 40 mm; the height of the water distribution layer is 40 mm, and a perforated (aperture 2 mm) water distribution pipe is used on the upper part of the water distribution layer to evenly distribute water; the height of the main layer is 120 mm; and the height of the filter layer is 80 mm.
[0058] The schematic diagram of the biofilter is shown in Figure 1 .
[0059] (2) Determine experimental conditions and methods
[0060] The flow rate of the experimental device (each plexiglass column) was set to 710 μL / min, and the hydraulic retention time was 5.9 h (the influent was simulated wastewater). Before the experiment was officially put into operation, a rapid biofilm method was used to conduct microbial domestication and biofilm formation for two months (the sludge from the aeration tank of the sewage treatment plant was inoculated in the main layer and the filter layer for microbial domestication and biofilm formation, and the sludge concentration was about 3000 mg / L). The effluent indicators were measured every day, and the first stage of the experiment was carried out after the effluent water quality was stable. The experimental water was simulated wastewater prepared with glucose (nutrients), ammonium chloride, sodium nitrate, sodium nitrite, potassium dihydrogen phosphate and trace elements necessary for microbial growth; it lasted for 2 to 3 days. When the effluent was stable and reached the initial effluent water quality concentration of the first stage (ammonia nitrogen and total nitrogen removal rates reached about 30%), the cultivation and domestication (biofilm formation) was successful.
[0061] The main water quality parameters of influent (simulated wastewater) are shown in Table 1.
[0062] In stages I and II, glucose was added as a carbon source to control the C / N ratio to about 4:1, and in stages III to V, the C / N ratio was about 1:2. Only in stages II and III, the influent was aerated intermittently, and the influent DO was 6.5-8.0 mg·L -1 ; No aeration was performed in the remaining stages, and the inlet DO was 4.2-5.6 mg·L -1 The water temperature in stages I to IV (influent water temperature) was 20±1.7°C, and the water temperature in stage V (influent water temperature) was 15.3±2.2°C. The influent pH was 7.13±0.43, and the effluent pH was 7.37±0.56.
[0063] Table 1 Average values of main water quality parameters of influent (simulated wastewater) at each stage (mg·L -1 )
[0064] stage <![CDATA[NH4 + -N]]> <![CDATA[NO3 - -N]]> <![CDATA[NO2 - -N]]> TN TP Ⅰ 22.93 - - 22.93 0.81 Ⅱ 25.82 - - 25.82 0.81 Ⅲ 25.86 - - 25.86 0.79 Ⅳ - 14.41 - 14.41 - Ⅴ - 2.08 5.13 7.21 -
[0065] Water is collected from the sampling port every day, filtered through a 0.45μm filter membrane, and its water quality analysis indicators are measured. + -N: Nanoscale reagent spectrophotometry; NO3 - -N: UV spectrophotometry; NO2 - -N:(1-naphthyl)-ethylenediamine spectrophotometric method; PO4 3- : Ammonium molybdate spectrophotometry. Water temperature, DO and pH were measured using a portable dissolver (JPB-607). Total inorganic nitrogen (TN) content was obtained by summing up various forms of nitrogen.
[0066] (3) Effect of nitrogen and phosphorus removal
[0067] 1) NH4 + -N removes the effect
[0068] The removal of ammonia nitrogen by each biofilter is shown in Figure 2 (a) Figure and Table 2.
[0069] In the first stage, the ammonia nitrogen removal rate of each reactor was relatively low, with an average removal rate of about 30%. The main reason was that it was the initial stage of the reactor operation and the content of nitrifying bacteria was relatively low. Another reason was that the dissolved oxygen concentration in the water was relatively low and nitrification was inhibited.
[0070] In the second stage, the ammonia nitrogen removal effect of each reactor was improved. The average ammonia nitrogen removal rates of the four reactors EF-A, EF-B, EF-C and EF-D were 43.63%, 63.13%, 36.77% and 37.73%, respectively.
[0071] In stage III, under low carbon-nitrogen ratio simulated tail water, the ammonia nitrogen effluent concentrations of the four reactors did not change much compared with the previous stage.
[0072] The ammonia nitrogen removal effect in EF-B was significantly better than that in the other three reactors. The adsorption of biochar may be one of the reasons. The fact that zero-valent iron (iron powder) can improve the nitrification efficiency in the aerobic stage may be the main reason. The addition of pyrite in EF-C and EF-D caused the dominant microorganisms to change, which may have an ecological competition with nitrifying bacteria, affecting the activity of nitrifying bacteria and the efficiency of nitrification.
[0073] Table 2 Nitrogen removal rate (%)
[0074]
[0075] In stage III, under low carbon-nitrogen ratio simulated tail water, the ammonia nitrogen effluent concentrations of the four reactors did not change much compared with the previous stage.
[0076] 2) NO X - -N removes the effect
[0077] from Figure 2 As can be seen from Figure (b), in stage I, the nitrate nitrogen concentrations in the four reactors were all below the detectable range. The reason is that the removal rates of ammonia nitrogen in the four reactors were all low, resulting in a low accumulated nitrate nitrogen content (not reflected in Figure (b)). In stage II, the ammonia nitrogen removal rates of each reactor were improved, and the concentration of nitrate nitrogen generated by the conversion intermediate increased. Nitrate nitrogen accumulated in the EF-A and EF-B reactors, while the EF-C and EF-D reactors were still below the detectable concentration of nitrate nitrogen. The effluent concentration of nitrate in EF-B was lower than that of EF-A, indicating that the combined application of iron powder and biochar enhanced biological denitrification.
[0078] In phase III, it was found that a large amount of nitrate nitrogen accumulated in the EF-A reactor (4.41 mg·L -1) because the lack of carbon source in the EF-A reactor inhibited denitrification, resulting in a large accumulation of nitrate nitrogen. Compared with the EF-A reactor, the effluent nitrate nitrogen of the EF-B reactor was at a lower concentration (0.70 mg·L -1 ), the combined application of iron powder and biochar can enhance the nitrate removal efficiency of low C / N tail water. The effluent concentration of EF-C and EF-D was 0.30 mg·L -1 The reason is that pyrite can participate in autotrophic denitrification and cooperate with iron powder and biochar to further enhance the denitrification performance.
[0079] In the IV stage, the nitrate nitrogen removal rates of each reactor were 7.68%, 57.98%, 95.64% and 98.45%. The EF-B reactor showed a good effect compared with the EF-A reactor because biochar can provide carbon source to a certain extent; on the other hand, zero-valent iron (iron powder) can promote the removal of nitrate nitrogen. Compared with EF-B, the removal rates of EF-C and EF-D increased by 37.66% and 40.47%, respectively, which further shows that pyrite, iron powder and biochar have a synergistic effect on enhancing denitrification.
[0080] In stage V, the nitrate nitrogen in the influent mainly comes from the oxidation of the added sodium nitrite. The nitrate nitrogen removal rate of EF-A did not change significantly, while the removal rates of EF-B, EF-C, and EF-D decreased by 29.65%, 65.51%, and 21.62% respectively compared with the previous stage. This is because NO3 - The removal rate of -N decreases with decreasing temperature, while EF-D is relatively less affected by temperature (which may be related to its chemical nitrate removal mechanism).
[0081] from Figure 2 As can be seen from Figure (c), NO2 - -N effluent concentration changes. In the first four stages, nitrite nitrogen in the water is an intermediate product generated by nitrification and denitrification. The nitrite nitrogen content in the effluents of the four reactors was low, with no significant difference. In stage V, sodium nitrite was actively added to the influent, and the removal rates of the four reactors were 7.04%, 27.99%, 28.33%, and 60.72%; the EF-D reactor was significantly better than the other three groups of reactors. EF-C and EF-D underwent autotrophic denitrification based on pyrite, and at the same time, the release of carbon source by biochar promoted autotrophic denitrification, forming a synergistic effect of heterotrophic autotrophic denitrification. Compared with EF-D and EF-B, it can be seen that the addition of pyrite can significantly improve the nitrite removal rate.
[0082] 3) TN removal effect
[0083] from Figure 2As can be seen in Figure (d), in stages I to III, the denitrification performance of EF-B is better than that of the other three groups of reactors because of its good nitrification performance, while the denitrification effects of EF-C and EF-D are not obvious, mainly because of the poor nitrification effect. In stage IV, the TN removal rate of EF-B is 57.81%, which is significantly higher than that of EF-A at 7.40%. This is because zero-valent iron (iron powder) can remove nitrate nitrogen through chemical reactions, and biochar provides carbon sources to synergize iron autotrophic denitrification to remove nitrate nitrogen; EF-C (TN removal rate is 95.04%) is 37.23% higher than EF-B, and EF-D (TN removal rate is 98.04%) is 3.00% higher than EF-C, because the addition of pyrite strengthens the autotrophic denitrification of sulfur bacteria. In stage V, due to the decrease in temperature, the TN removal rates of each reactor decreased to varying degrees, but the EF-D reactor still showed a high TN removal rate (65.42%). The denitrification effect of modified expanded clay filler in EF-D is significantly better than the existing single pyrite denitrification and zero-valent iron and pyrite (FeS2) combined denitrification research results, indicating that the coupling effect of zero-valent iron, pyrite and biochar is better for denitrification.
[0084] 4) Phosphorus removal effect
[0085] Depend on Figure 3 As can be seen from Table 3, in stage I, the EF-C reactor had the highest TP removal rate of 56.79%. In stage II, the TP removal rates of each reactor increased to varying degrees, namely 69.12%, 79.85%, 74.77%, and 86.02%, respectively. In the EF-B, EF-C, and EF-D reactors, iron ions can combine with phosphate to remove phosphate as precipitation; the adsorption of iron hydroxide precipitates also promotes further removal of phosphorus. In addition, the adsorption of biochar in the transition layer and the formation of Ca5(OH)(PO4 3- )5 precipitation, also played a certain role in phosphorus removal. In the third stage, the removal effect of TP in each reactor decreased. On the one hand, the lack of carbon source inhibited the biological activity of polyphosphate bacteria; on the other hand, the accumulated nitrate nitrogen in the water inhibited the release of phosphorus under anaerobic conditions. The EF-D reactor was least affected, indicating that the addition of pyrite is helpful for the phosphorus removal of low-carbon wastewater.
[0086] Table 3 Phosphorus removal rate (%)
[0087] stage EF-A EF-B EF-C EF-D Ⅰ 50.50 44.64 56.79 43.42 Ⅱ 69.12 79.85 74.77 86.02 Ⅲ 54.04 55.14 51.68 69.03
[0088] 4) Phosphorus removal effect
[0089] (4) Analysis of the mechanism of enhanced nitrogen and phosphorus removal
[0090] 1) Denitrification mechanism
[0091] The removal of nitrate nitrogen of the present invention is mainly through the following three effects, traditional denitrification, iron autotrophic denitrification based on zero-valent iron and pyrite, and sulfur autotrophic denitrification. Traditional denitrifying bacteria are anaerobic heterotrophic bacteria, and their conversion of nitrate nitrogen strictly depends on the carbon source. When the C / N is relatively low, it is not conducive to the denitrification and denitrification. The present invention, by inoculating aerobic denitrifying bacteria, synergistically exerts the nitrification and denitrification effect, thereby improving the removal effect of nitrate nitrogen. In addition, biochar is added to the modified ceramsite filler used in the present invention, and the organic matter released by biochar can provide a carbon source for microorganisms, which can compensate for the influence of the inhibition of denitrification under low C / N (lack of carbon source) to a certain extent, and the enrichment of biochar can promote the distribution of denitrifying bacteria communities to promote the denitrification process. The added zero-valent iron (iron powder) can enhance the relative abundance of denitrifying bacteria in iron-based biological systems, improve denitrification efficiency, and reduce the consumption of organic carbon.
[0092] In the iron-carbon micro-electrolysis system, iron and biochar act as electrode materials to form a large number of micro-batteries, and then Fe(II) and [H] are formed during the reaction. They are highly active and can decompose most organic pollutants, and the high [H] production rate can also promote the metabolism of autotrophic denitrifying bacteria.
[0093] Anode: Fe-2e - →Fe 2+ (1)
[0094] Cathode: O2+4H + +4e - →2O · +4[H]→2H2O (2)
[0095] The autotrophic denitrification based on pyrite can be expressed by equations (3) and (4);
[0096]
[0097]
[0098] Fe(0) removes NO3 - -N process involves both chemical and biological reactions. The chemical reaction converts NO3 - -N is converted to NH4 + -N (Equations (5) and (6)), while the biological reaction uses H2 produced by Fe(0) corrosion under anaerobic conditions as an electron donor, NO3 - -N is an electron acceptor to generate N2 (Eq. (7), (8)). On the one hand, Fe(0) can react with FeS2 to produce Fe 3+ Reaction to increase Fe 2+concentration (Equation (9)), thereby realizing the Fe(III) / Fe(II) cycle; on the other hand, the Fe in the modified ceramsite filler 2+ Provides more electrons for denitrification; increasing iron ions can accelerate the electron transfer rate of autotrophic denitrification, thereby improving denitrification performance.
[0099]
[0100] Fe 0 +2H2O→H2+Fe 2+ +2OH - (7)
[0101]
[0102] Fe 0 +2Fe 3+ →3Fe 2+ (9)
[0103] In summary, the traditional denitrification, iron autotrophic denitrification, sulfur autotrophic denitrification and biochar enrichment of microorganisms in the present invention synergistically enhance the denitrification effect on low C / N ratio wastewater and enhance the denitrification performance of the system.
[0104] 2) Phosphorus removal mechanism
[0105] The biofilter of the present invention has two phosphorus removal methods: chemical phosphorus removal and biological phosphorus removal. Biological phosphorus removal is mainly based on the enhanced biological phosphorus removal theory (Enhanced biological phosphorus removal, EBPR). Polyphosphate bacteria release and absorb phosphorus under alternating anaerobic and aerobic conditions and convert it into polyphosphate in the cell, and remove phosphorus by removing phosphorus-rich sludge. Iron is added to the modified ceramsite filler used in the present invention. Iron is an essential element for microbial growth. It is an important component of cytochrome in the biological oxidase system. It plays an electron transfer role in biological oxidation, has a certain promoting effect on bacterial reproduction and enzyme secretion, and can promote microbial growth and phosphorus removal. Chemical phosphorus removal, on the one hand, is through the adsorption of phosphorus by the filter layer limestone, and on the other hand, iron ions and their hydroxides also play an important role in phosphorus removal. In addition, biochar adsorption also plays a corresponding phosphorus removal role. The added pyrite can be used as an electron donor for sulfur autotrophic denitrification to carry out iron-carbon micro-electrolysis, which promotes autotrophic denitrification to generate iron ions, thereby improving phosphorus removal efficiency.
[0106]
[0107] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A modified ceramsite filler based on iron-sulfur autotrophic denitrification, characterized in that: The modified ceramsite filler is ceramsite loaded with a modified substance; The ingredients of the amendment include iron powder, pyrite powder and biochar; The mass ratio of the iron powder, pyrite powder and biochar is 3:6:1; The mass ratio of the modifier to the ceramsite is 1.5:
1.
2. A method for preparing the modified ceramsite filler according to claim 1, characterized in that: The following steps are involved: Iron powder, pyrite powder, biochar and cement are uniformly mixed to obtain a modified substance, the modified substance is attached to ceramsite, and the modified ceramsite filler is obtained after curing.
3. The preparation method according to claim 2, characterized in that: The curing time is 10 to 12 days; the particle size of the modified ceramsite filler is 5 to 8 mm; and the amount of cement used is 20% of the total mass of iron powder, pyrite powder and biochar.
4. Use of the modified ceramsite filler according to claim 1 in sewage treatment.
5. The use according to claim 4, characterized in that: The sewage is sewage containing nitrogen and phosphorus.
6. A biofilter for removing nitrogen and phosphorus from sewage, characterized in that: The modified ceramsite filler described in claim 1 is used as the main layer.
7. The biofilter according to claim 6, characterized in that: The biofilter is provided with a main body layer and a filter layer; The sewage first passes through the main layer and then the filter layer; The thickness ratio of the main layer to the filter layer is 3:2; The filter layer is composed of limestone and biochar in a mass ratio of 9:
1.
8. The biofilter according to claim 7, characterized in that: The particle sizes of the limestone and biochar are both 3-5 mm.
Citation Information
Patent Citations
Coupling filler autotrophic denitrification biofilter and application
CN109052641A
Secondary biochemical effluent sulfur-iron synergistic polyculture denitrification deep nitrogen removal method
CN113321297A
Autotrophic and heterotrophic synergistic denitrification biological carrier as well as preparation method and application thereof
CN117342698A
Iron-pyrite-zeolite composite filter tank device for ultimate nitrogen and phosphorus removal
CN117682599A
Advanced nitrogen removal method and device for sewage with low carbon nitrogen ratio coupled with pyrite autotrophic denitrification
CN118545836A
Cited By
Pyrite Fenton-like catalyst, preparation method thereof and application of pyrite Fenton-like catalyst in red tide treatment
CN119972177A
Low-carbon-nitrogen-ratio sewage and wastewater synchronous nitrification and denitrification-polyculture denitrification nitrogen and phosphorus removal method and reactor
CN120157258A
Biofilter electrode filler laying method and device for synchronous nitrogen and phosphorus removal and N2O emission reduction of low-carbon-nitrogen-ratio sewage
CN121063687A
Pyrite-activated carbon composite constructed wetland filler based on agricultural wastes as well as preparation method and application of pyrite-activated carbon composite constructed wetland filler
CN121181130A
Preparation method of composite filler for synchronously removing composite pollutants in municipal sewage
CN121377313A